Hubungan Karateristik Orang Tua Dan Pengetahuan Gizi Dengan Konsumsi Sayur Dan Buah Siswa Di Sma Kristen Mercusuar Kupang - Haru, Aprianus; Zogara, Asweros Umbu; Demu, Yohanes Don Bosko (Poltekkes Kemenkes Kupang, 2025)
The period between childhood and adulthood, known as adolescence, is marked by a number of social, mental, and physical changes. Rapid increases in height and weight are indicators of adolescent physical development. Due to changes in body composition and nutrient excess or deficiency, nutritional needs increase during this phase. To determine the relationship between parental characteristics and nutritional knowledge with students' consumption of vegetables and fruits at Mercusuar Kupang Christian High School, the research instruments were questionnaires and the study was quantitative research using the observational method with a cross-sectional design. To see the relationship between parental characteristics and nutritional knowledge with students' vegetable and fruit consumption, the data was analyzed using the Chi-Square Test. The results of the univariate analysis showed that 53 students (43.8%) had good knowledge, 55 students (45.5%) had sufficient knowledge, and 13 students (10.7%) had poor knowledge. The most common educational background of the fathers was high school graduates, with 60 people (49.6%), while the most common educational background of the mothers was high school graduates, with 58 people (47.9%). Regarding the parents' occupations, the most common occupation for fathers was self-employed, with 53 people (43.8%). For mothers, the most common occupation was homemaker, with 53 people (43.8%). Based on bivariate analysis, there was no significant correlation between the mother's education level and vegetable consumption (p-value 0.937), no significant correlation between the father's education level and vegetable consumption (p-value 0.127), and no significant correlation between nutrition knowledge and vegetable consumption (p-value 0.137) and fruit consumption (p-value 0.137). However, for fruit consumption (p-value 0.885), there was a relationship between the father's occupation and vegetable consumption (p-value 0.005 ≤0.05), but there was no relationship with fruit consumption (p-value 0.682). There was no significant relationship between the mother's occupation and vegetable consumption (p-value 0.997), while for fruit consumption (p-value 0.434). Suggestion: For Mercusuar Kupang Christian High School, continue to provide education and motivation to adolescents so they can apply existing nutrition knowledge more effectively. The results of this research are expected to be used as a consideration for making policies on school children's nutrition services, such as establishing a canteen at school that offers affordable vegetables and fruits.Keywords: Student knowledge, Education, Parental occupation